2007
DOI: 10.1051/0004-6361:20077900
|View full text |Cite
|
Sign up to set email alerts
|

The velocity structure of moving magnetic feature pairs around sunspots: support for the U-loop model

Abstract: Context. Moving magnetic feature (MMF) pairs are among the most significant fine-scale structures around sunspots. Several models have been proposed to interpret the origin and evolution of MMF pairs. These models provide important clues to understanding MMF pairs. Aims. We present an analysis of the velocity structure of MMF pairs in order to put further constrains on the MMF models. , and on average, the velocity of an MMF pair decreases significantly (from 0.6 km s −1 to 0.35 km s −1 ) with increasing dista… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Hagenaar & Shine (2005) found that MMFs begin at high velocities of 1.8 km s −1 near the outer boundary of the penumbra, which is faster than average moat velocities. Zhang et al (2007) also found an outward decrease in flow velocity of MMFs from 0.6 km s −1 to 0.35 km s −1 . Sainz Dalda & Martínez Pillet (2005) and Ravindra (2006) found that MMFs originate in the outer penumbra.…”
Section: Introductionmentioning
confidence: 75%
“…Hagenaar & Shine (2005) found that MMFs begin at high velocities of 1.8 km s −1 near the outer boundary of the penumbra, which is faster than average moat velocities. Zhang et al (2007) also found an outward decrease in flow velocity of MMFs from 0.6 km s −1 to 0.35 km s −1 . Sainz Dalda & Martínez Pillet (2005) and Ravindra (2006) found that MMFs originate in the outer penumbra.…”
Section: Introductionmentioning
confidence: 75%
“…This supports the ''sea serpent'' concept for MMFs, whereby the horizontal penumbral fields undulate into and out of the solar surface ( Harvey & Harvey 1973;Schlichenmaier 2002). Many authors have proposed that the fluctuating penumbral fields and the subsequent MMFs are produced by Evershed flows (e.g., Ryutova et al 1998;Martínez Pillet 2002;Thomas et al 2002;Schlichenmaier 2002;Zhang et al 2003Zhang et al , 2007bCabrera Solana et al 2006). On the other hand, MMFs located on the lines extrapolated from the penumbral spines have magnetic fields that are more vertical than those of their surroundings (Kubo et al 2007a).…”
Section: Introductionmentioning
confidence: 82%
“…Their magnetic configuration must be that of a -loop, since this is the shape of the field lines in the bipolar structures while they still reside in the penumbra. Zhang et al (2007) and Cabrera have deduced a similar configuration for bipolar MMFs. Our interpretation of the observations is summarized in Fig.…”
Section: Discussionmentioning
confidence: 98%